Straw yield and cover crop weed suppression in a no tillage system for processing tomato - Silva, Andréia Cristina da; Hirata, Edson Kiyoharu; Monquero, Patrícia Andréa (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to evaluate the straw yield, the weed suppression, and the effects of cover crop species on processing tomato (Lycopersicon esculentum) yield, in no tillage system. The treatments evaluated were Crotalaria juncea, Stizolobium aterrimum, Pennisetum glaucum, C. juncea + P. glaucum, C. juncea + S. aterrimum, P. glaucum + S. aterrimum, spontaneous weed cover, and bare soil. The experimental design was randomized complete blocks with four replicates. The tomato yield was not influenced by cover crops. C. juncea was more competitive than P. glaucum, when intercropped, with larger dry mass accumulation (63%). S. aterrimum had slow initial development and low competitivity with the high weed infestations. P. glaucum and C. juncea, grown alone, together, or with S. aterrimum, had dry matter yield above 20 Mg ha-1 and reduced the emergence and dry matter accumulation of weeds in the processing tomato crop.